An Overview Of Terrestrial Gastropods in India - CYRIL, ALEENA ELIZABETH; JOSEPH, GIGI K. (Indian Forester, 2023)
Terrestrial gastropods which comprise snails, slugs and semi-slugs form a significant invertebrate taxon that performs several crucial ecosystem services as detritlvores, pollinators, seed dispersal agents, calcium reserves and as part of the food web. But very often gastropods are mentioned under the infamous tag of pests and vectors. Terrestrial gastropods have been associated with human culture as food, subsistence tools and decorations. They have tremendous economic potential. They can be used as bioindicators of various ecosystem attributes like leaf litter and soil biodiversity, pollution, soil calcium levels and habitat disturbances. India being one of the 'megadiverse' countries with its diverse ecosystems, tropical climate and monsoon has so far recorded only 1129 species of terrestrial gastropods with 1109 snail species and 20 slug species. Terrestrial gastropods of Western Ghats show high endemism of 76%. The terrestrial gastropods form a neglected Invertebrate taxon In terms of biodiversity assessments and conservation measures In India.